Food Vendors Mapping in Three Sublocations of Vihiga County, Kenya: A Food Environment Study (July–August 2023) - Maina, Evalyn Waruguru; Aluso, Lillian Olimba; Wanyama, Rosina Nanjala; Termote, Celine; Akingbemisilu, Tosin Harold (2025)
This study aims to understand the food environment by examining both formal and informal food vendors in selected villages and markets of Vihiga County. The Primary data was collected through a food vendor mapping and census by use of a semi-structured questionnaire deployed using ODK.This study aims to understand the food environment by examining both formal and informal food vendors in selected villages and markets of Vihiga County. The Primary data was collected through a food vendor mapping and census by use of a semi-structured questionnaire deployed using ODK. Metodology:The survey employed a multi-stage sampling technique, enabling sequential sampling across multiple hierarchical levels. In the first stage, Vihiga County was purposively selected, encompassing all food vendors as the study population. In the second stage, three sub-locations—Ebungangwe, Emanda, and Mwitubwi—situated in Emuhaya, Vihiga, and Luanda Sub-Counties, respectively, were purposively chosen. Vendors in villages within these sub-locations and nearby markets were comprehensively mapped. The study relied on primary data collected directly from food vendors in Vihiga County.The survey employed a multi-stage sampling technique, enabling sequential sampling across multiple hierarchical levels. In the first stage, Vihiga County was purposively selected, encompassing all food vendors as the study population. In the second stage, three sub-locations—Ebungangwe, Emanda, and Mwitubwi—situated in Emuhaya, Vihiga, and Luanda Sub-Counties, respectively, were purposively chosen. Vendors in villages within these sub-locations and nearby markets were comprehensively mapped. The study relied on primary data collected directly from food vendors in Vihiga County.